ANALISIS DAYA DUKUNG PERAIRAN BANYUPUTIH TERHADAP LIMBAH TAMBAK UDANG BERDASARKAN VOLUME AIR YANG TERSEDIA DI PERAIRAN - Abdul Muqsith (Faculty of Science and Technology University Ibrahimy, 2015)
The purpose of this study was to determine the ability of coastal waters Banyuputih know in accepting waste shrimp farm activities based on the volume of water available in retail waste from shrimp farms. Research conducted in the coastal region of Subdistrict Banyuputih Situbondo from September 2013 until February 2014 by using descriptive method. The data used in this study consisted of two (2) types of primary data and secondary data. Primary data was collected through observation / measurements and interviews at locations other research and secondary data obtained from the literature search in various institutions associated with research materials. The analysis showed that the volume of water available in coastal waters Banyuputih able to accommodate or resell the waste produced amounted to 515,142.6 m3 shrimp farms. If converted in the pond area, the area of ​​ponds that can be supported waters is 515.1 ha. At this time there was activity shrimp farms in coastal areas still under the maximum carrying capacity of receiving waters in the waste. The area of ​​the pond has recently reached 113 ha. Potential embankment land in coastal areas Banyuputih still be developed in accordance waters carrying capacity of 402 ha.